Museums in a digital age. - Parry, Ross (Leicester readers in museum studies., 2010)
The influence of digital media on the cultural heritage sector has been pervasive and profound. Today museums are reliant on new technology to manage their collections. They collect digital as well as material things. New media is embedded within their exhibition spaces. And their activity online is as important as their physical presence on site. However, ‘digital heritage’ (as an area of practice and as a subject of study) does not exist in one single place. Its evidence base is complex, diverse and distributed, and its content is available through multiple channels, on varied media, in myriad locations, and different genres of writing. It is this diaspora of material and practice that this Reader is intended to address. With over forty chapters (by some fifty authors and co-authors), from around the world, spanning over twenty years of museum practice and research, this volume acts as an aggregator drawing selectively from a notoriously distributed network of content. Divided into seven parts (on information, space, access, interpretation, objects, production and futures), the book presents a series of cross-sections through the body of digital heritage literature, each revealing how a different aspect of curatorship and museum provision has been informed, shaped or challenged by computing. Museums in a Digital Age is a provocative and inspiring guide for any student or practitioner of digital heritage -- Présentation de l'éditeur.